Perioperative Pain Management for One Day Surgery (ODS) and Minimally Invasive Surgery (MIS) by the Royal College of Anesthesiologists of Thailand - Manuwong, Sudsayam (Thai Journal of Anesthesiology, 2021)
Pain is one of the common causes of delayed discharge after one day surgery and minimally invasive surgery. This practice guideline has been developed for effective perioperative pain assessment and management, leading to patient safety and recovery, reducing the complications and pain dissatisfaction. This practice guideline may be adjusted as appropriate when more evidence available, including new technologies in the future. However, this practice guideline can be adapted according to the context of each hospital or institution.